A tectonically driven Ediacaran oxygenation event - Joshua J. Williams (Nature Portfolio, 2019)
The evolution of complex animal life in the Cambrian period is thought to be related to oxygenation of the Earth System, however the timing, magnitude and mechanism of this oxygenation event remain uncertain. Here, the authors use a biogeochemical model which links tectonic CO2 degassing rates to carbon and sulphur burial, and suggest that atmospheric pO2 increased by ~50% during the Ediacaran Period.